1999
DOI: 10.1046/j.1420-9101.1999.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and gene flow in a northern willow tit (Parus montanus) population

Abstract: To study quantitatively the relationship between immigration rate and gene flow we used 9‐year data from a willow tit Parus montanus population in a continuous forest habitat. We compared components of lifetime reproductive success, and parental survival rate between immigrant and resident (‘status’) birds by taking individual age into consideration also. Of the fitness components, survival was independent of status and sex, averaging 0.60 annually. Of the male and female breeders, on average 63.1% and 75.6%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 60 publications
2
70
0
1
Order By: Relevance
“…The dopamine receptor D4 gene (DRD4) has been of interest for some years owing to its role in novelty seeking or exploratory behaviour in animals and is one of the most profound 'personality genes' known in humans, and a singlenucleotide DNA polymorphism in DRD4 predicts some of the variation in exploratory behaviour of Great Tits (Korsten et al 2010). These kinds of developments underpin the genetic basis of behaviour relevant to dispersal, consistent with suggestions that long-distance dispersal seems heritable (Orell et al 1999;Hansson et al 2004). The potential for human impacts to radically alter the distribution of such genes is considerable and could have substantial demographic impacts.…”
Section: The Genomics Revolution and Associated Technical Advancementioning
confidence: 68%
See 1 more Smart Citation
“…The dopamine receptor D4 gene (DRD4) has been of interest for some years owing to its role in novelty seeking or exploratory behaviour in animals and is one of the most profound 'personality genes' known in humans, and a singlenucleotide DNA polymorphism in DRD4 predicts some of the variation in exploratory behaviour of Great Tits (Korsten et al 2010). These kinds of developments underpin the genetic basis of behaviour relevant to dispersal, consistent with suggestions that long-distance dispersal seems heritable (Orell et al 1999;Hansson et al 2004). The potential for human impacts to radically alter the distribution of such genes is considerable and could have substantial demographic impacts.…”
Section: The Genomics Revolution and Associated Technical Advancementioning
confidence: 68%
“…There was evidence that inbreeding depression was associated with the lower LRS of philopatric females, and the deficit in recruitment for long-distance dispersing females may have resulted from local maladaptation or their offspring being especially prone to long-distance dispersal outside the study area, or a combination of the two. In the Willow Tit (Poecile montanus) a similar pattern of low local recruitment in offspring of longdistance dispersing mothers was attributed to greater offspring dispersal rather than a fitness deficit, on the basis that those that recruited locally had normal fitness (Orell et al 1999). Although these studies indicate that gene flow and demographic impacts of long-distance dispersal may be somewhat lower than expected from the number of immigrants, long-distance dispersal remains of critical importance in recolonisation of habitat patches, functioning of meta-populations, and dispersal and gene flow, particularly through systems modified by human impacts (Trakhtenbrot et al 2005).…”
Section: Estimating Dispersalmentioning
confidence: 99%
“…Orell et al (1999) found respective mean NDDs of 1601 m and 1787 m for male and female Willow Tits P. montana in northern Finland. The estimation of dispersal distances for this species in Sweden were hampered by low rates of subsequent detection of birds ringed as nestlings; a problem also found with Siberian Tits in Finland P. cinctus and Black-capped Chickadees P. atricapilla in British Columbia (Smith 1967, Ekman 1979, Virkkala 1990).…”
mentioning
confidence: 80%
“…These studies show that, in birds, philopatric individuals often are equal or superior to immigrants (Clobert et al 1988;Pärt 1994;Verhulst and van Eck 1996; but see Orell et al 1999;Marr et al 2002). We have previously shown that this generality applies also to the great reed warbler (Acrocephalus arundinaceus; Bensch et al 1998).…”
mentioning
confidence: 94%